GUNNERA MORAE (GUNNERACEAE), A NEW SPECIES FROM COLOMBIA - WANNTORP, LIVIA; KLACKENBERG, JENS (Caldasia, 2006)
A Colombian species of Gunnera, G. morae L. Wanntorp & Klackenberg, previously mistakenly identified as Gunnera manicata Linden ex André, is presented and described. Molecular phylogenetic studies as well as morphological evidence have shown this plant to be different from the Brazilian true G. manicata.